2007
DOI: 10.1002/jor.20411
|View full text |Cite
|
Sign up to set email alerts
|

Bone formation following OP‐1 implantation is improved by addition of autogenous bone marrow cells in a canine femur defect model

Abstract: Osteogenic Protein-1 (OP-1, BMP-7) acts locally on connective tissue progenitors (CTPs) to induce bone formation. The response to OP-1 and similar agents is potentially limited by the number of local CTPs. This study tested the hypothesis that supplementing local CTPs using autogenous bone marrow will enhance bone formation at an OP-1 implant. Four 1.0-cm diameter unicortical cylindrical defects in the left proximal femur were grafted in each of seven dogs. Radial ingrowth of new bone formation was assessed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 34 publications
0
32
0
Order By: Relevance
“…[22][23][24] The left femur was exposed in an extraperiosteal plane by elevating the vastus lateralis. A customized drill template was fixed longitudinally on the lateral aspect of the femur with two 3.5-mm bicortical screws.…”
Section: Canine Femoral Multidefect Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24] The left femur was exposed in an extraperiosteal plane by elevating the vastus lateralis. A customized drill template was fixed longitudinally on the lateral aspect of the femur with two 3.5-mm bicortical screws.…”
Section: Canine Femoral Multidefect Modelmentioning
confidence: 99%
“…The value of directly comparing two grafting techniques in single animal controls for variation between subjects and increases statistical power by offering paired comparisons, which in turn reduce the number of subjects needed to address a given comparison. [22][23][24] Defect sites and performance are reproducible. Very importantly, the defects are large enough so that the center of the defect will become profoundly hypoxic within 2-3 days following surgery.…”
mentioning
confidence: 99%
“…Similarly, in a dogs study, the simultaneous application of rhBMP-7 and MSC has increased the local population of cells and the connective tissue progenitors in a canine femur defect model (21). In another study conducted on tibial critical size defects ofmini-pigs, it has been revealed that area of new bone formation was significantly higher in the group treated with an association of PRP and ABG compared with the group treated with the application of ABG alone.…”
Section: Resultsmentioning
confidence: 84%
“…The CFMD model has been shown to be an effective tool for comparison of cell sourcing and processing strategies, 48 and methods involving growth factor delivery use. 38 The CFMD model is currently being evaluated for use in assessment of methods to optimizes the microenvironment for cell transplantation (e.g., the use of platelet gel preparations), and the selective surface modification of biomaterials (e.g., presentation of tethered growth factors).…”
Section: Discussionmentioning
confidence: 99%
“…The canine femoral multi-defect (CFMD) model 37,38 was used for these studies. The CFMD model provides four 10-mm-diameter and 15-mm-long defects for assessment in each subject.…”
Section: Canine Femoral Multi-defect Modelmentioning
confidence: 99%